Going off the grid: ERα breast cancer beyond estradiol. (July 2016) - Perone, Ylenia; Magnani, Luca
Abstract : Novel studies have linked cholesterol biosynthesis to drug resistance in luminal breast cancer. Structural data suggest that cholesterol metabolites, including 27-hydroxycholesterol (27HC), can act as ERα ligands in these cells. Additionally, hypercholesterolemia has now been linked to breast cancer progression. The focus of this review is to briefly summarize these recent findings and discuss how epigenetic reprogramming is definitively connected to endogenous cholesterol biosynthesis. We elaborate on how these data support a working model in which cholesterol biosynthesis promotes autocrine, pro-invasive signaling via activation of a series of closely related transcription factors. Importantly, we discuss how this mechanism of resistance is specifically associated with aromatase inhibitors. Finally, we examine how the field is now considering the development of anticholesterol therapeutics and companion biomarkers to stratify and treat ERα breast cancer patients. In particular, we review recent progress in pharmaceutical strategies targeting the cholesterol molecular machinery in primary and secondary breast cancers.